Ángel Ferrant`s teaching beginnings: an early vocation - Asenjo Fernández, Ignacio (Arte, Individuo y Sociedad, 2009)
The sculptor Ángel Ferrant took part in the variety of events associated with education in art. His pedagogical vocation encouraged him to combine his artistic practice with teaching. He believed that the educational system of his time should be modernized in order to achieve the longed-for artistic transformation. Before becoming famous for being a reformer of the artistic pedagogy in Spain, he had to undergo some training and undertake a long teaching career, full of valuable experiences. Some of his ideas or initial proposals about certain aspects related to art teaching will evolve with the passage of time.
Keywords: Ángel Ferrant; Teaching beginnings; Art Education; Pedagogical reformism; Didactic comparisons